Continuous Casting Practices for Steel: Past, Present and Future - Roderick I. L. Guthrie; Mihaiela M. Isac (Metals, 2022)
This historical review of casting methods used to produce sheets of steel for automobiles, household products, rocket bodies, etc., all point toward the development of one-step commercial processes, which are capable of casting liquid steel directly into a final sheet product. Progress towards this goal is confirmed by successful advances being made, but there remain major difficulties in reaching it. We concur that the conventional continuous casting method remains the current process of choice for highest-quality steel sheet products, but the ESP TSC (Endless Strip Production—Thin Slab Caster) approach is now highly competitive. Similarly, the original goal of Sir Henry Bessemer to produce a direct strip-making twin-drum caster, in 1856, finally came to lasting commercial fruition at CASTRIP/NUCOR. Nonetheless, a newer approach, promoted by Salzgitter, termed DSP (Direct Strip Production), or promoted by MMPC/MetSim as HSBC (Horizontal Single Belt Casting), has several advantages over CASTRIP in terms of microstructures and productivity. As such, the pros and cons of current methods are reviewed within this brief history of casting.